Accountability And Transparency Analysis Of Local Government Financial Performance (Study of Regional Apparatus Organizations (OPD) in Pohuwato Regency) - Sitti Rizqi Aulia Rasyid; Harun Blongkod; Herlina Rasjid (Dhana, 2024)
Since the implementation of performance-based budgeting, all local governments have been obligated to create good financial performance of their local governments. As such, financial performance is one of the most significant topics to be studied in public sector organizations, including the government. the growing calls from public sector entities including national and local governments and government work units for the adoption of public accountability. The purpose of this study is to ascertain how accountability and transparency affect local governments' financial performance. This study employs a quantitative methodology. Purposive sampling is the method used in the sampling process. In order to collect primary data for this study, 210 respondents were given questionnaires. The study's conclusions demonstrate that: 1) Accountability has a positive and significant impact on the local government's financial performance; 2) Transparency has a positive and significant impact on financial performance; and 3) Accountability and Transparency have a significant impact on the Pohuwato Regency Regional Government's financial performance at the same time.